Measuring judiciarization of people with mental illnesses - Mikhaylova, Oxana (Crime, law and social change, 2022)
The judiciarization of the psychiatric subject is a two-sided process. It could anti-discriminate people with mental illnesses but, at the same time, it could potentially provoke pathologization of mental illnesses. Current methodologies proposed to measure this important and complicated process for people with mental illnesses do not allow analysis on multiple levels (the macro, meso, and micro). In this article, to fill this gap we propose a methodological strategy that helps to investigate judiciarization of people with mental illnesses on multiple levels at once. This approach is based on critical discourse analysis of legal documents and court decisions that feature people with the poor mental health. Namely, we suggest how to measure the level or degree of judiciarization, its geographical evenness, actors in the legal process, its dimensions (the law branches of its occurrence), and linguistic content. We applied this methodology in examining 1,243 legal documents and 327,311 court decisions that were issued by agents of the Russian law system. The research findings show that judiciarization levels in Russia have been rising over the years, moving away from stigmatizing those with mental illnesses and towards anti-discrimination. Our paper could be of interest to socio-legal researchers and social policy practitioners.